Investigation on the Influence of Cutting Parameters on Machining Performance during Turning of Difficult-to-Machine Steels - Anthony Xavior, M.; Adithan, M. (Applied Science and Engineering Progress, 2013)
The influence of cutting parameters viz. cutting speed, feed rate and depth of cut, tool geometry viz. rake angle, clearance angle and nose radius on turning of AISI 304 stainless steel, AISI 52100 bearing steel and AISI D2 tool steel with advanced cutting tools like multicoated carbide, cermet and alumina inserts are investigated experimentally. The machining performance (i.e. output parameters) considered in this article are surface roughness, flank wear and tool-shim interface temperature. Experiments are conducted according to Taguchi’s orthogonal array and ANOVA is performed to evaluate the significance of each of the input parameters on each of the output parameters. It is found that variation in work materials, and tool materials have significant effect on flank wear apart from cutting speed. Tool cutting edge geometry like nose radius and clearance angle influenced surface roughness apart from the cutting parameters. Variations in work material, cutting fluids and nose radius have considerable influence on tool-shim interface temperature